An interproximal model to determine the erosion-protective effect of calcium silicate, sodium phosphate, fluoride formulations. Issue 2 (February 2018) - Wood, Natalie J.; Jones, Siân Bodfel; Chapman, Nick; Joiner, Andrew; Philpotts, Carole J.; West, Nicola X.
Highlights: An interproximal model can detect the protective effects of anti-erosion products. Calcium silicate/sodium phosphate toothpastes protect against interproximal erosion. A toothpaste gel combination increases protection against frequent acid exposure. Abstract: Objectives: Previous work has shown the effectiveness of a newly developed interproximal model to differentiate between the amount of remineralization caused by toothpastes used with or without a dual-phase gel treatment system containing calcium silicate, sodium phosphate salts and fluoride to repair acid-softened enamel. The aim of this study was to utilize the same interproximal model to identify how effective calcium silicate phosphate toothpastes are at reducing surface softening in the early stages of erosion. The model was also used to identify the effect of increasing the frequency of acid exposure on the reduction in surface hardness. Methods: Human enamel specimens were prepared and mounted in an interproximal face-to-face arrangement and exposed to a cycling regime of whole human saliva, treatment, artificial saliva and 1% citric acid pH 3.75. Specimens were measured by surface microhardness at baseline and after three and seven days. The frequency of acid exposure was increased from 2 to 4 cycles a day for the second part of the study. Results: The results showed that specimens treated with the calcium silicate phosphate toothpastes softened less than those treated with control fluoridated or non-fluoride toothpastes at each time point and following an increase in the frequency of acid exposure. Significance: This work has demonstrated how an interproximal model can also be successfully used to determine differences in the erosion protection of various treatments as well as determining how they perform when the frequency of acid exposure is increased.